Determinants of healthcare service utilization among enrolled residents of the negros occidental comprehensive health program - Reteracion, Jacquiline T.; Trajera, Sheilla M.; Chua, Loresita Antonia A.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
This study explored the extent of healthcare service utilization among residents enrolled in the Negros Occidental Comprehensive Health Program (NOCHP), focusing on seven key indicators: predisposing factors, enabling factors, perceived need, accessibility, continuity, comprehensiveness, and coordination. Anchored in Andersen and Newman’s Behavioral Model and Starfield’s Primary Care dimensions, a quantitative descriptive design was used, with data collected from 315 volunteer participants. A modified version of the Primary Care Assessment Tool guided the evaluation of the indicators. Findings revealed that predisposing factors, perceived need, continuity, comprehensiveness, and coordination were strong indicators of utilization, while accessibility and enabling factors were moderate. Significant differences in utilization were observed across age, gender, education, income, and occupation, but not by marital status. These results highlight the complex interplay of demographic and systemic factors influencing healthcare access and use. The study provides evidence-based insights to support improvements in provincial health programs and serves as a reference for policymakers, administrators, and researchers aiming to strengthen public healthcare delivery for insured populations.